Evaluation of MicroRNA‐146a and Its Targets in Gingival Tissues of Patients With Chronic Periodontitis. Issue 12 (1st December 2015) - Motedayyen, Hossein; Ghotloo, Somayeh; Saffari, Mahmood; Sattari, Mandana; Amid, Reza
Abstract : Background: MicroRNAs (miRNAs) are a group of small non‐coding RNAs that play an important role in the regulation of gene expression. miRNA‐146a (miR‐146a), a member of the miR‐146 family, is involved in the control of inflammation. Periodontitis is a set of chronic inflammatory disorders of the tissues surrounding the teeth that lead to the breakdown of alveolar bone and tooth loss. In this study, expression levels of miR‐146a and its targets, including tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, and IL‐6, are evaluated in human patients with chronic periodontitis (CP). Methods: The study population consisted of 10 healthy controls and 20 individuals with CP. For each participant, clinical parameters including probing depth and clinical attachment level were measured, and a gingival tissue sample was collected. Levels of miR‐146a, TNF‐α, IL‐1β, and IL‐6 were quantified using real‐time polymerase chain reaction. Results: Levels of miR‐146a were significantly higher in patients with CP ( P <0.001). There was a positive correlation between levels of miR‐146a and clinical parameters ( P <0.05). Elevated miR‐146a was accompanied by a significant reduction in TNF‐α and IL‐6 ( P <0.001). Conclusions: Patients with CP had higher levels of miR‐146a than healthy individuals, accompanied by reduced levels of TNF‐α and IL‐6. A positive relationship between miR‐146a levels and clinical parameters suggests a pathophysiologic role of miR‐146a in CP.